Design Metal Detecting Arduino Remote Control Robot Vehicle Controlled via Bluetooth - R., Jeyagopi; Chan, C.K.; M.I.N, Ma'arof (INTI International University, 2022)
In today’s world, robotics is fast-growing and already interacting in many aspects of our daily lives. Robotic is part of the communication of advancement of technology, engineers have decided to work in this field to design or build robots that will make human life more advanced. There are several types of mobile robotics in today’s technology world. There are tracks robots, humanoid robots, water-based robots, wheels robots and etc. Thus, a metal detecting remote control robot vehicle is designed using four wheels in this research. The system is implemented using the Arduino platform, android application, and metal detector winding. This robot vehicle has been developed with the interaction of an Android-based device. Arduino Uno is used as the brain of the robot. It also includes the part of the software that utilizes a portable application. In this paper, a metal detecting robot is designed to allow the robot vehicle to detect the metal and the robot vehicle control via Bluetooth remote control. The proposed design is compared with the automated robot in terms of accuracy of detection, turning, and costing. The results show that the proposed design robot vehicle is able to provide an accurate and fast in detecting the metal movement, easier in turning, and cheaper.